2016
DOI: 10.1002/pits.21947
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parental Divorce or a Father's Death on High School Completion

Abstract: Associations between parental loss and high school (HS) completion were examined in data drawn from 1,761 male and 1,689 female offspring born in wedlock to mothers participating in a nationally representative study. Multiple logistic regression models were conducted predicting HS completion by age 19 among offspring whose parents divorced or father died, compared to offspring of continuously married parents. Models were estimated without and with adjustment for correlated sociodemographic characteristics, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
3
10
0
Order By: Relevance
“…The educational consequences of parental death were found to be smaller than those of parental divorce, and overall were comparable for children of lowerand higher-educated parents. This confirms ideas from previous studies suggesting that after parental death, children may face a smaller loss in resources and obtain substantial support from family and friends, who (to some extent) take over the role of the deceased parent (Albertini and Dronkers 2009;Sapharas et al 2016;Steele, Sigle-Rushton, and Kravdal 2009).…”
Section: Conclusion and Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The educational consequences of parental death were found to be smaller than those of parental divorce, and overall were comparable for children of lowerand higher-educated parents. This confirms ideas from previous studies suggesting that after parental death, children may face a smaller loss in resources and obtain substantial support from family and friends, who (to some extent) take over the role of the deceased parent (Albertini and Dronkers 2009;Sapharas et al 2016;Steele, Sigle-Rushton, and Kravdal 2009).…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…Although both experiences lead to family stress, due to either the loss of a parent or conflict between parents, the reduction of resources may be less profound for children who face parental death (Biblarz and Gottainer 2000). This is because in families where a parent has died, children often receive support from extended family members and friends of the deceased parent, who take over some parenting duties and support children's educational attainment (Albertini and Dronkers 2009;Sapharas et al 2016;Steele, Sigle-Rushton, and Kravdal 2009). Children of divorced parents, however, tend to have much less contact with their nonresident parent, as well as that parent's family and friends over time, providing less opportunity to compensate for the loss in parental resources and support (Steele, Sigle-Rushton, and Kravdal 2009;Westphal, Poortman, and Van der Lippe 2015).…”
Section: Educational Consequences Of Parental Death or Divorcementioning
confidence: 99%
See 1 more Smart Citation
“…Jørgensen et al (2018) found that educational attainment was negatively affected in a group of bereaved children, as they were 61% more likely to attain the lowest educational level. Sapharas et al (2016) concurred with this finding, as they demonstrated that paternal death predicted a 79% decrease in the likelihood of completing high school among female students. A register-based Norwegian study conducted by Burrell et al (2020) explored the impact of parental death on education based on 373,104 individuals, of whom 3,692 had experienced parental death due to external causes (eg accidents, homicides, and suicides) before the age of 18.…”
Section: Educational Attainment and Gradessupporting
confidence: 70%
“…In line with previous research we use parental death as second comparison group to explore the driving mechanisms (e.g., Amato and Anthony 2014; Biblarz and Gottainer 2000;Cherlin, Kiernan, and Chase-Lansdale 1995;Sapharas et al 2016). On the one hand, one might expect that the consequences of parental death are similar to children who lived with both parents because parental death is thought to be considerably more random than parental separation.…”
Section: Parental Separation Parental Death and The Importance Of Gen...mentioning
confidence: 99%